Green detection of the olive fruit fly pest by the direct determination of its sexual pheromone. Issue 17 (7th September 2015) - Alcudia-León, María del Carmen; Cárdenas, Soledad; Valcárcel, Miguel; Lucena, Rafael
<x xml:space="preserve">Abstract</x> Bactrocera oleae Gmelin, the olive fruit fly, is considered a serious pest in the cultivation of olive trees since the larvae feed on the fruit damaging the productivity and quality of the final products (olive fruit and olive oil).